Afrojin: racialidade e afrossaberes na escola - Almeida, Joria Ane Lima Batista (2024)
The purpose of this study was to understand and value the contributions made by Sociology to ethnic-racial relations, Africanities and racial self-identification of young students based on pedagogical interventions in a public and professional school in the State of Ceará. From the debates held at school on the concepts of discrimination, prejudice, segregation, racism, anti-racism, ethnicity and multiculturalism, several concerns were raised by the students. I noticed, beyond doubts, the difficulty in expressing racial belongings, a silence in the face of knowledge related to Afro-Brazilian religions. Such concerns later formed the problems that underlie the research. During classes I presented different black references in the study of Anthropology such as: Kabengele Munanga and Lélia González. From the trajectory of these authors, I noticed greater engagement with the theme as excerpts from the authors' works were presented and the students noticed themselves in these productions. A group of students came to me interested in finding out more about black authors and so we started conversations during breaks about them – thus creating the genesis of what we would call AFROJIN. In general, the pedagogical intervention - AFROJIN - that underpins the research took place in 2021, in a school located in Guaiúba (CE) and, in addition to specific action, we sought to plan and execute an interdisciplinary project on this theme aiming to provide the opportunity for Sociology teachers to outline new ways to encourage student autonomy based on the importance given to the suggestions and problems listed by students. The project was developed through workshops and learning meetings that made it possible to share more significant knowledge.